ANALISIS KETENAGA KERJAAN PADA BEBERAPA PABRIK KAYU LAPIS DI SUMATERA DAN KALIMANTAN - Akub J Abdurachman; Sylviani Sylviani (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
An analysis of man power has been conducted in several plywood mills in Sumatera and Kalimantan in year 1987, and the result presented in this paper. The result shows that the average employment is 993 men per mill.Based on mill capasity and log input, the average level of labour absorption is 11.33 men/1000 cum designed capasity, and 10.66 men/1000 cum log input. The latter figure is more or less similar to that of the developed country in which the average level of labour absorption is.11.33 men/1000 cum. However labour absorption in each mill it is not proportional to both capasity and material utilization (logs). Organization structure of mills surveyed have a long span of control so it is recommended to be simplified.